2007
DOI: 10.1029/2006gl028468
|View full text |Cite
|
Sign up to set email alerts
|

Direct polymerization of isoprene and α‐pinene on acidic aerosols

Abstract: [1] The direct polymerization of isoprene and a-pinene on acidic sulfate aerosols has been studied in a reaction chamber utilizing aerosol mass spectrometry. Results indicated that both species can be directly taken up into acidic aerosols to a significant extent, forming polymers that contain at least 4 isoprene or 2 a-pinene repeating units. Aerosol mass spectra indicate that double bonds in the polymers hydrate under acid catalysis, leading to partial oxygenation of the polymers. This reactive uptake depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
71
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(85 citation statements)
references
References 19 publications
13
71
1
Order By: Relevance
“…It has been shown recently that on highly acidic particles even the direct uptake of isoprene and α-pinene is possible, i.e. without any prior photooxidation step (Liggio et al, 2007), confirming the hypothesis based on previous bulk experiments (Limbeck et al, 2003).…”
Section: Introductionsupporting
confidence: 85%
“…It has been shown recently that on highly acidic particles even the direct uptake of isoprene and α-pinene is possible, i.e. without any prior photooxidation step (Liggio et al, 2007), confirming the hypothesis based on previous bulk experiments (Limbeck et al, 2003).…”
Section: Introductionsupporting
confidence: 85%
“…Edney, Kleindienst, and coworkers found similar results for isoprene photooxidation, with SOA yields greatly increased in the presence of SO 2 (which forms sulfuric acid aerosol upon oxidation) or H 2 SO 4 seed (Edney et al, 2005;Kleindienst et al, 2007b;Surratt et al, 2007b). Aerosol is also observed when high concentrations of isoprene are exposed to H 2 SO 4 seed in the absence of any oxidants (Limbeck et al, 2003;Liggio et al, 2007). These results likely arise from particle-phase reactions promoting SOA growth, in agreement with the conclusions of Jang et al (2002).…”
Section: Laboratory Measurements Of Aerosol Growth From Isoprene Oxidsupporting
confidence: 66%
“…The contribution of NO 3 to the total isoprene SOA is approximately 50% greater than OH in this regionally polluted area. However, this does not consider other possible routes for SOA formation from isoprene, such as heterogeneous reactions (Altieri et al, 2006;Ervens et al, 2008;Liggio et al, Analysis of several other flights showed correlations between nocturnally oxidized isoprene and observed WSOC, non-negligible contributions of NO 3 -isoprene SOA to total organic aerosol, and large nighttime isoprene-SOA compared to photochemical isoprene-SOA, as shown in Table 3. Figure 12 gives one additional example, from the night flight on 7 August which sampled mainly along the coastline from New Jersey to Massachusetts under conditions of offshore flow.…”
Section: Secondary Organic Aerosolmentioning
confidence: 99%